Research on work performance and job design in Southeast Asia countries: A publication review - Mohd Faizal, H.; Mohamad Noorman, M.; Muhamad Afiq Faisal, H. (2017)
Southeast Asia is a dynamic, competitive and full of expertise in various professions. The vibrant of working environment nowadays required employees to work hard and proactive. Performance and competence are key indicators to achieve the mission and vision of the organization. These situations transform the employees to work harder and multitask. As a result, employees are experiencing job stress and dissatisfaction with their working environment. Therefore, researchers are trying to discover what the elements that can motivate employees to excel. These scenarios increase the research on work performance and job design among the employees in the developed countries. Unfortunately, both concepts seem to be unpopular to study among the researchers in Southeast Asia countries. Some of the industries are totally ignoring job design in the work performance study. Furthermore, the numbers of literature searches on both concepts are very limited especially in library and information science. The objective of this paper is to identify a total of publication on work performance and job design among Southeast Asia researchers. The data was generated from few prominent databases. The data will help other researchers to study the factor contributing towards the aforementioned scenario.